Determinan Kejadian Penyakit Tuberkulosis (TB) Paru Di Provinsi Jawa Barat Tahun 2024 - Simbolon, Elsa; Alparizi. Z, M.; Khoirunnisa, Hasna Nur; Ulya, Wulan Septiani Shifaatul; Purwoto, Agus (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Pulmonary tuberculosis (TB) remains a significant public health concern in many countries, including Indonesia. West Java Province is one of the regions in Indonesia that bears a considerable burden in addressing pulmonary tuberculosis cases. The number of TB cases in this province has continued to rise, with 224,798 cases reported in 2024. This study aims to provide a general overview of the incidence of pulmonary tuberculosis in West Java in 2024 and to identify the variables that influence its occurrence. The analytical method used in this study is multiple linear regression. The study utilizes secondary data obtained from publications by Statistics Indonesia (Badan Pusat Statistik/BPS). The results show that the number of healthcare facilities has a significant effect on the incidence of pulmonary tuberculosis in West Java. In contrast, population density, the percentage of the poor population, and the percentage of livable housing do not have a significant effect on the incidence of pulmonary tuberculosis in the province.